Transarterial Treatment of Cranial Dural Arteriovenous Fistulas: The Role of Transarterial and Transvenous Balloon-Assisted Embolization - Zamponi, J.O. (AJNR Am J Neuroradiol, 2020)
BACKGROUND AND PURPOSE: Treatment of dural arteriovenous fistulas can be performed by transarterial or transvenous accesses. For those fistulas located at a dural sinus wall, obliteration of the sinus might lead to a substantial risk of complications if the occluded sinus impairs normal venous drainage. For those fistulas with direct leptomeningeal venous drainage, navigation to reach the arteriovenous shunting point of a leptomeningeal vein is usually technically demanding. We report the outcomes of patients with dural AVFs treated by transarterial injection of liquid embolic agents assisted by transarterial double-lumen balloon catheters and/or transvenous balloon catheters. MATERIALS AND METHODS: This was a retrospective, 3-center study including patients with dural AVFs treated with a balloon-assisted technique in at least 1 treatment session. Angiographic follow-up was performed at 6 months. Clinical assessment was performed at admission and discharge and was reassessed at 30-day and 6-month follow-ups. RESULTS: Forty-one patients with 43 dural AVFs were treated. Thirty-four fistulas were located at a dural sinus wall. Treatment was performed using only a transarterial approach in 42 fistulas. Only 1 session was needed for complete obliteration of the fistula in 86% of the patients. Immediate complete angiographic occlusion was achieved in 39 fistulas. Of the 41 controlled fistulas, 40 (97.6%) were completely occluded at 6 months. Thirty-nine fistulas (95.1%) were cured without any report of major neurologic events or death during follow-up. CONCLUSIONS: Transarterial balloon-assisted treatment of dural AVFs with or without transvenous balloon protection was shown to be safe and effective.